2010
DOI: 10.1063/1.3386510
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial engineering and coupling of electric and magnetic properties in Pb(Zr0.53Ti0.47)O3/CoFe2O4 multiferroic epitaxial multilayers

Abstract: Epitaxial magnetoelectric ͑ME͒ Pb͑Zr 0.53 Ti 0.47 ͒O 3 ͑PZT͒ / CoFe 2 O 4 ͑CFO͒ multilayer nanocomposite thin films with up to 11 alternative layers are grown on Nb doped SrTiO 3 ͑STO͒ substrates by pulsed-laser deposition. X-ray diffraction and high resolution transmission electron microscopy studies reveal a good epitaxial relationship between the PZT and CFO layers without interfacial reaction at their interfaces. These epitaxial composite films exhibit strong ferroelectric and magnetic responses simultaneo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(15 citation statements)
references
References 35 publications
(36 reference statements)
2
13
0
Order By: Relevance
“…This was reflected in the loss tangent (tan ı, ı is the phase angle) curves, where well-defined and symmetrical peaks were observed. These peaks shifted to higher frequencies with an increase in temperature and exhibited distributions of Debye-like relaxation processes, which is consistent with the Maxwell-Wagner relaxation dispersion model [22][23][24]. A decrease in ε with increasing frequency was also noticed and this might be due to the dipole (space-charge) lags behind the applied field at high frequencies.…”
Section: Dielectric Analysissupporting
confidence: 74%
See 1 more Smart Citation
“…This was reflected in the loss tangent (tan ı, ı is the phase angle) curves, where well-defined and symmetrical peaks were observed. These peaks shifted to higher frequencies with an increase in temperature and exhibited distributions of Debye-like relaxation processes, which is consistent with the Maxwell-Wagner relaxation dispersion model [22][23][24]. A decrease in ε with increasing frequency was also noticed and this might be due to the dipole (space-charge) lags behind the applied field at high frequencies.…”
Section: Dielectric Analysissupporting
confidence: 74%
“…These point charges result in an additional space charge polarization i.e. Maxwell-Wagner (MWtype) relaxation in the frequency range (10 Hz to 1 MHz) [23,24]. Therefore, it is reasonable to assume that the peak is originated from the Maxwell-Wagner polarization between the PZT phase with higher resistivity and the NZFO phase with much lower resistivity.…”
Section: Impedance Analysismentioning
confidence: 97%
“…In this respect, ME composite thin films [6] comprised of layered FE and FM materials [7,8] are of special interest due to their potential applications in ME random access memories [9] and ME microsensors [10]. To date, the ME effect has be extensively reported on in multiferroic layered structures in which the state-of-the-art FE perovskite Pb(Zr 1-x Ti x )O 3 (PZT) is paired with the hard magnetic spinel-ferrite CoFe 2 O 4 [11,12]. Typically, the observed ME coupling in piezoelectric/magnetostrictive PZT/CFO bilayered films has been attributed to their interfacial strains [13]: the presence of the CFO layer imposes an in-plane tensile stress on the PZT layer across the interface, increasing the interactive stress between the CFO and PZT layers and hence the ME coupling [6].…”
Section: Introductionmentioning
confidence: 99%
“…The dielectric dispersion at lower frequency can be explained by Maxwell-Wagner interfacial polarization theory [14,15]. It was reported by Zhang et al [17] that they used Maxwell-Wagner space charge model to calculate in comparison with the experimental observation and concluded that the peak of dielectric loss at a relatively low frequency should be originated from the space charge effect in the PZT/CFO multilayer capacitors. In addition, it can be further observed that the dielectric loss increases as Fig.…”
Section: Methodsmentioning
confidence: 93%